2007
DOI: 10.1016/j.pain.2006.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Classical conditioning and expectancy in placebo hypoalgesia: A randomized controlled study in patients with atopic dermatitis and persons with healthy skin

Abstract: The effectiveness of placebos is unchallenged. However, it is still not clear on which mechanisms the placebo effect is based. Besides expectancy theories, classical conditioning is discussed as a major explanatory model. In an experimental conditioning design we tested 96 participants, 48 with atopic dermatitis (24 male, 24 female) and 48 with healthy skin (24 male and 24 female). All of them received a neutral ointment with a different briefing ("pain-reducing ointment" versus "neutral ointment"). Electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
91
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 29 publications
11
91
1
5
Order By: Relevance
“…The question whether the placebo effect depends more on classical conditioning or on cognitive processes was directly examined in several studies (Benedetti et al 2003a, b;Price et al 1999). Conditioning theorists have proposed that the placebo is a conditioned Pavlovian response, whereas others have advocated that the placebo is driven by expectancy (Kirsch 2004;Klinger et al 2007;Rescorla 1988;Stewart-Williams and Podd 2004;Wager and Nitschke 2005). The placebo analgesia effect investigated in this study might be brought about mainly through expectation.…”
Section: Discussionmentioning
confidence: 87%
“…The question whether the placebo effect depends more on classical conditioning or on cognitive processes was directly examined in several studies (Benedetti et al 2003a, b;Price et al 1999). Conditioning theorists have proposed that the placebo is a conditioned Pavlovian response, whereas others have advocated that the placebo is driven by expectancy (Kirsch 2004;Klinger et al 2007;Rescorla 1988;Stewart-Williams and Podd 2004;Wager and Nitschke 2005). The placebo analgesia effect investigated in this study might be brought about mainly through expectation.…”
Section: Discussionmentioning
confidence: 87%
“…They showed that conditioning supports the maintenance of placebo responses in a patient population. Additionally, the authors demonstrated that the patient's history plays an important role in the formation of placebo responses [53]. Patients have a completely different history of exposure to medications and healing experiences, suggesting that the prior experience of those who interpret placebos as sign vehicles have differential impacts on the formation of placebo responses.…”
Section: Conditioning and Prior Experience (A) Classical Conditioningmentioning
confidence: 99%
“…For example, in patients with pain, placebo mechanisms may involve the release of endogenous opioids 2 and endogenous cannabinoids 3 ; in patients with Parkinson's disease, placebo mechanisms may involve the release of dopamine. 1 Such mechanisms, in turn, may depend on expectancy and classical conditioning 4 ; after all, if the sound of a bell can trigger salivation or if the sight of food can stimulate the secretion of gastric juices, then perhaps the sight of a doctor's office, the swallowing of a colored pill, or the prick of a syringe may trigger the release of the appropriate chemicals for the relief of pain, anxiety, or depression. Nevertheless, what the placebo mechanism is in complex psychiatric disorders is poorly understood.…”
Section: Why Patients Improve With Treatment: the Effects Of Medicatimentioning
confidence: 99%